Strength, Weaknesses, Opportunities, and Threats (SWOT) Analysis of CV Rejeki Mapan Lestari - Teguh Sriwidadi; Juwita Gautama (Bina Nusantara University, 2016)
The objectives of this research were to identify the strengths, weaknesses, opportunities, and threats faced by CV Rejek Mapan Lestari, and to establish the appropriate strategies that should be applied to the company to evolve the company business. The research was conducted with a descriptive method, the researcher gathered the data with two medium, questionnaire and interview followed by the extraction method using various way such as IFE Matrix, EFE Matrix, SWOT/TOWS, IE Matrix, and QSPM Matrix which result in various alternative strategies that could be the viable option for the company. It can be concluded that CV Rejeki Mapan Lestari is highly advised in using a product development strategy by extending product variant and adding product that meet the markets need, for instance plastic flake.